USULAN RENCANA PENGUKURAN KINERJA STRATEGI BISNIS DENGAN MENGGUNAKAN KERANGKA THE BALANCED SCORECARD PADA PT PERTAMINA GAS (PERSERO) - Wardhana, Aditya (JURNAL KEBANGSAAN, 2013)
The measurement of business performance are still focusing on financial performance as net profit, cost minimization, maximization of existing outputs and the measurement of assets that are tangible, it will not be able to measure the value of penciptaaan assets are intangible. The purpose of this research is to develop a performance measurement framework that is balanced, coherent, and comprehensive on the company which is engaged in the business of gas such as PT Pertamina Gas (Persero) by using the methods of the balanced score card. The research method used is descriptive analysis with a combination of quantitative and qualitative approaches. Data obtained from observation, interview, questionnaire, and a study of the literature. Data analysis and interpretation results illustrate that management companies have the same perception that to improve overall corporate performance starts from the perspective of learning and growth. Keywords : The Balanced Scorecard